Path analysis of physical and psychological determinants of mawashi geri performance in kempo - Nori Meristika; Yendrizal Yendrizal; Alnedral Alnedral; Ridho Bahtra (Global Econedu, 2026)
This study aimed to examine the direct and indirect effects of lower-limb explosive power, foot-eye coordination, and concentration on mawashi geri kicking performance among Kempo athletes. A quantitative causal-associative design was employed involving 22 male senior Kempo athletes selected through purposive sampling. Lower-limb explosive power, foot-eye coordination, concentration, and mawashi geri performance were assessed using standardized field tests. Data were analyzed using descriptive statistics, assumption testing, and path analysis with IBM SPSS Statistics 26. Lower-limb explosive power (β = 0.460, p = 0.031), foot-eye coordination (β = 0.539, p = 0.010), and concentration (β = 0.555, p = 0.007) significantly influenced mawashi geri performance. Collectively, these variables explained 48.5% of performance variance (R² = 0.485). Integrated physical and psychological training emphasizing explosive power, coordination, and concentration is essential for optimizing mawashi geri performance in competitive Kempo athletes